Obliteration Rate of Arteriovenous Malformation by Radiosurgery - Mohd Zamri, Sarah Atiqah; Mohd Ali, Mohd Raffiz; Mohamad, Siti Azleen; Ghani, Abdul Rahman Izaini; Idris, Zamzuri; Abdullah, Jafri Malin (Malaysian Journal of Medical Sciences, 2025)
Background: The main goal of any arteriovenous malformation (AVM) intervention is to eliminate the risk of haemorrhage, which can be achieved by complete extirpation, endoluminal occlusion, or obliteration of the AVM. Radiosurgery is a minimally invasive intervention that can be performed alone or in combination with other treatments. This study aimed to determine the rate of AVM obliteration in our study population and to explore the effect of AVM characteristics, treatment mode, and treatment parameters on the obliteration rate.Methods: Three centres participating in this study obtained approval from the institutional review board and ethics committee. A total of 104 patients from among 146 were identified according to the inclusion and exclusion criteria. Data retrieved from each centre includes demographic review, AVM characteristics such as size, volume, location, eloquence, venous drainage, aneurysm association, treatment mode, and parameters. Univariate and multivariate logistic regression analyses were performed to determine the potential predictors of clinical outcome, AVM obliteration, and early obliteration.Results: Of the 104 patients who underwent radiosurgery, 45 (43.3%) were obliterated, and 88.9% were obliterated within three years. The independent predictors of AVM obliteration were low Spetzler-Martin grading (P = 0.005), dose > 22 Gy (P = 0.001), low radiosurgery-based AVM grading scale score (P = 0.037), low Virginia radiosurgery AVM scale score (P = 0.045), fraction (P = 0.002), and treatment mode (P = 0.025). Volume was the independent predictor of early obliteration (P = 0.013). The presence of a neurological deficit was the independent predictor of the clinical outcome (P = 0.018).Conclusions: Identifying predictors of good outcomes for patients who are suitable for radiosurgery is important to ensure optimal AVM treatment.